Read Between the Walls. Spatial Dimensions of the Hidden School (EAAE Annual Conference Proceedings, 2019)
Architecture matters. The space where education takes place matters. The spatial dimension of a school transforms an abstraction into a situated phenomenon. In doing so, the context intentionally or implicitly affects education.The potential impact the physical environment and the implied connotations it carries on one’s experience in and of it, is best argued by common sense. Consider the following example.A wall is a boundary marker. Its function varies: to protect, to enclose, to constrain, to separate and differentiate between spaces, to redirect and flank. Erecting a wall, however, is an intentional design gesture, affiliated to the formation of a barrier, a division, a fortification and/or isolation. Those purposeful and associative properties of a wall are translated into one’s embodied experience of a physical wall.
Keywords: spatial dimension; walls and spaces; environmental psychology; social phenomenology